Cross-school collaboration in the Finnish archipelago through Virtual Learning Environments - Charlotta Hilli (University of Aberdeen, School of Education, 2020)
In this feature, I present implications from a cross-school project in the Finnish archipelago (2015-17). Three primary schools and five teachers collaborated with the researcher to extend their classrooms through a Virtual Learning Environment (Fronter, Blackboard Collaborate). Data were analysed with the theory of practice architectures. The schools were part of complex arrangements on several levels that had implications for the success of the remote teaching initiative: classroom level (e.g. digital competence), school level (e.g. joint teacher positions, faculty support) and regional level (e.g. school transport, relevant digital infrastructure).